The end of book and the beginning of reading: electronic books and iPad phenomenon - Cordón-García, José-Antonio (Anuario ThinkEPI, 2011)
Ebooks have undergone a spectacular development in the past two years, extending their success beyond the forecasts of specialists. Attest to this digital reading statistics, the growth of the publishing offer, and the increased reading devices sales. One interesting thing has been the emergence of the iPad, a device introduced in early 2010 that, although it is not specifically devoted to reading, it has been discovered as one of the preferred e-readers. The importance of the phenomenon is in the fact that major publishers and authors, and large media groups are producing applications and products for exclusive use in this device. In contrast to static and mimetic reading of traditional books, there are new products and ways of digital reading with multimedia features.